2018
DOI: 10.1002/jmv.25015
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophil‐to‐lymphocyte ratio associated with prognosis in HBV‐infected patients

Abstract: Chronic severe hepatitis B (CSHB) is a critical clinical syndrome with a high mortality rate in China. The prognostic value of neutrophil to lymphocyte ratio (NLR) which is simple, low-cost, and useful inflammatory marker for hepatitis B virus (HBV)-infected patients is largely overlooked and without further exploration. This study assesses the association of NLR with prognosis of chronic hepatitis B (CHB) and CSHB patients. Two hundred and eighty subjects, including 79 with chronic hepatitis B (CHB) and 67 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Similar to the work by H. Liu et al, the current study found a negative correlation between NLR and disease aggravation [3]. J. Gong et al presents results consistent with the presented observations, indicating that NLR is reversely correlated with disease aggravation [11]. Higher values of this marker were observed in more severely sick patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to the work by H. Liu et al, the current study found a negative correlation between NLR and disease aggravation [3]. J. Gong et al presents results consistent with the presented observations, indicating that NLR is reversely correlated with disease aggravation [11]. Higher values of this marker were observed in more severely sick patients.…”
Section: Discussionsupporting
confidence: 92%
“…In chronic hepatitis B, the NLR was evaluated in this study as a predictive factor for hepatic fibrosis and steatosis. Attempts were made to introduce the NLR into the diagnostics and monitoring of such diseases as Hodgkin's lymphoma [4,5,6], diffuse large B-cell Lymphoma [7], gastric cancer or acute venous thrombosis [8,9,10,11]. Furthermore, everyday clinical practice is faced with the so-far underestimated problem of liver steatosis.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis virus infection is widely known as a common cause of liver cancer. Related studies revealed that the peripheral NLR of patients with chronic hepatitis B is positively correlated with disease severity and mortality (161). A recent study showed that HBV infection can inhibit the release of NETs from neutrophils by regulating the levels of cellular ROS and autophagy to maintain chronic liver inflammation (162).…”
Section: Liver and Biliary Cancermentioning
confidence: 99%
“…Hepatitis B virus (HBV) is an enveloped virus belonging to the hepadnaviridae family and possessing a partially double‐stranded circular DNA genome . HBV infection is one of the major global public health problems with over 240 million chronically infected individuals worldwide . Chronic hepatitis B virus (CHB) infection is correlated with high risk of developing liver fibrosis, cirrhosis, and hepatocellular carcinoma .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 HBV infection is one of the major global public health problems with over 240 million chronically infected individuals worldwide. 3 Chronic hepatitis B virus (CHB) infection is correlated with high risk of developing liver fibrosis, cirrhosis, and hepatocellular carcinoma. 4,5 Currently, interferon-α (IFN-α) is one of the most commonly used treatment for HBV infection.…”
Section: Introductionmentioning
confidence: 99%